A review on factors affected marital adjustment among parents of autistic children and gender effects - AlHorany, Ahmed Kamel; Hassan, Siti Aishah; Bataineh, Marwan Zaid (Marsland Press, 2013)
We aimed to systematically review studies that examine factors affecting marital adjustment among parents of children with disabilities, especially the autistic children. Besides, we emphasized the effects of gender on marital adjustments among the parents. There were at least 20 articles reviewed. The related journal articles on factor affecting marital adjustments were downloaded with cut off limit from 1992 to 2012. The articles were then analyzed and organized according to the definitions of marital adjustments and various factor affecting marital adjustments. We found there was no conclusive evidence regarding the factors affecting the marital among parents of autistics children. There was conclusive evidence from the reviewed literature regarding gender effect, yet the number of article supporting it was small. Mothers of autistics children were more affected in the marital adjustments as compared to fathers. Finally, with conclusion we then suggest for future interventional study.